Analisis Kredit UMKM di Provinsi Aceh: Analisis Empiris Vector Error Correction Model (VECM) - Hamdani Hamdani; Ismail Ismail; Thasrif Murhadi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2020)
The purpose of this study was to determine the effect of regional gross domestic product, non-performing loans, and loan interest rates on credit absorption by SMEs in Aceh province in the long term. The data used is secondary data in the form of a quarter 1st quarter 1995 to third quarter 2015. The model used in this study is a model of Vector Error Correction Model (VECM) to find out the results of short-term estimates, and using Johansen cointegration test to determine the relationship long-term between variables. The data used in this study has been tested with Augmented Dickey Fuller (ADF) to determine the stationary data. Based on this study it was found that in the long term there is a cointegration relationship between the variables studied. In the short term, the variables affecting the gross regional domestic product and has a one-way relationship with SME loans while variable interest rates have a causal relationship with SME loans in Aceh province, while the NPL variable does not have a causal relationship with SME loans.